The Analysis of Risk Effect Towards Fintech Ecosystem On P2P Lending Industry in Indonesia - Wijaya, Chandra; Nugroho, Bernardus Yuliarto; Arkanuddin, Mohammad Fahmi (School of Business, IPB University (SB-IPB), 2022)
The purpose of this research for analyzing the affect and correlation risk to the fintech ecosystem on the P2P lending industry in Indonesia with the quantitative approach and using the analysis tools of SEM-Amos. The result is shown that risk has an affect and correlation significantly to the fintech ecosystem, it can prove that the risk changing has affect to fintech ecosystem stability. The key of activity on this industry is loan disbursement so the potential risk will come up is NPL (non-performing loan), which can cause credit risk. Credit risk can be mitigated by doing customer segmentation precisely. Mitigation is done by other risks, namely, operation, market, liquidity, legal, strategic, and pandemic risk-covid 19. Pandemic risk-covid 19 is an additional risk and positively correlates to start-up fintech elements. It is proof that the existence of pandemic-covid 19, the business of this industry is still running well and has no effect on it, causing this industry to use the mobile application and the transactions without meetings and still keep up social distancing. Another anticipation of empowering the fintech ecosystem by doing cooperation, coordination and collaboration between elements each other. This industry needs to add 2 (two) fintech ecosystem elements, they are credit insurance institutions and fintech consumer protection agency for anticipating the industry's need in the future. Keywords: fintech, fintech p2p lending, risk, pandemic risk-covid-19, fintech ecosystem